Finance for business : a guide for the lending banker - Checkley, Keith (London : Financial Training, 1988)
This book has been written principally for banking students, and bank managers' at the sharp end'. The principles outlined will apply to any business, whether new or existing, where the value of stock and cash flow relate to the cycle of production. The author takes an in-depth look at the various stages of business appraisal and discusses the key areas involved in assessing the business lending proposition. He explain credit control and monitoring, and shows how to reduce the risk of bad debts.
Includes bibliographical references and index.
hza 25/07/2018
Loans
Keywords: Business finance management; United Kingdom